EVALUASI PEMBELAJARAN MATEMATIKA BERBASIS PROYEK: EKSPLORASI PRAKTIK DAN TANTANGAN DI SMP NEGERI - Dodo Murtado; Hendro Prasetyono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore the practices and challenges of project-based mathematics learning (Project Based Learning/PBL) in a public junior high school. A qualitative approach was employed, using in-depth interviews and participatory observations, involving purposively selected informants: two mathematics teachers, one principal, and two students. Data analysis was conducted through data reduction, presentation, and conclusion/verification. The findings reveal that PBL implementation encourages active student engagement, develops 21st-century skills such as creativity, collaboration, communication, and critical thinking, and enhances deeper mastery of mathematical concepts. Teachers act as facilitators by preparing guides, adjusting projects to students’ abilities, and facilitating group discussions, while the principal supports the process through facilities, flexible learning spaces, and teacher training. Students respond positively, feeling motivated, confident, and more active in discussions and teamwork. Challenges identified include time management, teacher readiness, differences in student abilities, group cooperation, and limited facilities. Development strategies applied include task differentiation, step-by-step guidance, student reflection, teacher collaboration, and institutional support. With these strategies, PBL can be effectively implemented, providing meaningful and contextual learning experiences while stimulating 21st-century skills and overcoming existing challenges. This study offers practical insights for teachers and schools to optimize the implementation of project-based mathematics learning.